Risk factors for developing ventilator-associated pneumonia in patients admitted to the Intensive Care Unit (Research, Society and Development, 2021)
To analyze published scientific evidence on risk factors for developing ventilator-associated pneumonia in patients admitted to the Intensive Care Unit. This study is a literature review of the integrative literature review method, carried out in the months between May and October 2021. The search was carried out through the - VHL, using the LILACS, BDENF databases, through SCIELO. Adhering through the descriptors/key words: “Pneumonia”, “Mechanical Ventilation”, “Intensive Care Unit”, combined with the Boolean operator “AND”. Risk factors for VAP are advanced age above seventy years of age; with the; level of consciousness; intubation and tracheal reintubation; immune conditions; use of immunosuppressive drugs; shock; disease severity; advance of Chronic Obstructive Pulmonary Disease (COPD); prolonged period of mechanical ventilation greater than seven days; aspirated the contaminated condensate from the fan circuits; malnutrition; exogenous contamination; antibiotic therapy as prophylaxis; microbial colonization; prolonged surgeries; aspiration of contaminated secretions; gastric colonization and aspiration thereof, gastric pH (greater than 4). Nursing actions to control VAP are extremely important within the therapeutic and care context in the hospital. Continuing education and the adoption of measures based on scientific evidence, as well as health protocols, correspond to improvements in the aspects in question. Note the importance of the (NSP) and CCIH, which display indicators, inspection of sectors, development of protocols, prevention bundles, which are practices that have been proven to prevent VAP, permanent and continuing education activities linked to health promotion.